SELF-ESTEEM AS A PROTECTIVE FACTOR AGAINST FEAR OF MISSING OUT IN SOCIAL MEDIA ENGAGEMENT AMONG EMERGING ADULTHOOD - Carolina Ester Sopyana Tampubolon; Nuram Mubina; Yuwono Pratomo (EDUCATIONE, 2026)
This study aims to determine the effect of self-esteem on Fear of Missing Out (FoMO) on emerging adulthood of Instagram users in Karawang. FoMO is a feeling of anxiety when not connected to social activities that others do, as well as an urge to continue engaging in social experiences through social media. This study used a quantitative approach with 222 respondents in the age range of 18 to 25 years. The sampling technique used is convenience sampling. The measurement tool used in this study was adapted from Online Fear of Missing Out and adopted from the Rosenberg Self-Esteem Scale (RSES). The hypothesis test uses simple linear regression. The results showed that self-esteem had a negative effect on FoMO with a contribution of 17.3%. Individuals in emerging adulthood with high self-esteem tend to have lower levels of FOMO.